(untitled) (Hekima Review, 2008)
The prevalence and severity of sexual violence as well as its subsequent health and socio-economic consequences fundamentally change societies. Legal and social dimensions, such as women’s second-class status in the Congo and Liberia, actually support the use of rape and perpetuate its ruthless effects. While rape has been recognized as a war crime and a crime against humanity, very little is known about the protection strategies adopted by victims and their communities’ and how these strategies impact society. The context in which the violence occurs and the protection strategies employed by different communities must be better understood in order to develop holistic and effective solutions for bringing justice to the perpetrators of sexual violence and the care of victims.